Призраки в горах - Свиридов Тимур Георгиевич (Военные приключения, 2006)
Экземпляры: ф.4 (20151119) / Инвентарный номер: 2477 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 24 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44